Pengabdian Kepada Masyarakat Melalui Edukasi Kesehatan Melalui Penyuluhan Vitamin Di Posyandu Flamboyan Kota Batam - Hesti Marliza; Arie Vonikartika; Henny Rachdianti Tjahjono Suyarto; Nurlia Oktavianty (Pusat Riset dan Inovasi Nasional, 2021)
Vitamin A was the first fat-soluble vitamin to be discovered. This finding states that all retinoids and precursors/provitamin A/carotenoids have biological activity as retinol. Vitamin A plays an important role in children's growth and development. Vitamin A deficiency (KVA) increases the risk of developing infectious diseases such as diarrhea, pneumonia, pneumonia and even death. Another most serious consequence of vitamin A deficiency (KVA) is night blindness, which is another form of xeropthalmia such as damage to the cornea and blindness. Vitamin A can increase the body's resistance to infectious diseases such as measles, diarrhea and ARI and has a very important role in eye health.